Ion-paired antibiotics in PLGA nanoparticles: improving encapsulation efficiency and musculoskeletal infection treatment - Frolov, Vladislav; Sovány, Tamás; Loskot, Jan; Csapó, Edit; Varga, Norbert; Hassan, Alharith A A; Janďourek, Ondřej; Konečná, Klára; Bezrouk, Aleš; Šnejdrová, Eva (RSC advances, 2025)
Many studies have shown that gentamicin (GEN) and vancomycin (VAN) are effective in the treatment of musculoskeletal infections, especially when applied locally in the form of sustained-release drug delivery systems. A promising strategy in this area appears to be the impregnation of allogeneic bone grafts with antibiotics loaded poly(d,l-lactide-co-glycolide) (PLGA) nanoparticles (NPs). However, a major problem in formulating such systems is the high water solubility of these antibiotics, which leads to low drug content in NPs and rapid drug release. In this study, hydrophobic ion pairing (HIP) was employed to enhance the antibiotics loading and their prolong release from PLGA NPs. HIP complexes were formed using three anionic surfactants with bis(2-ethylhexyl) sulfosuccinate sodium salt (AOT) appearing to be the most effective. A novel potentiometric titration method was used to determine the optimal antibiotic-to-surfactant molar ratio. The VAN-AOT and GEN-AOT complexes were encapsulated into NPs prepared with non-commercial PLGA branched on either polyacrylic acid or tripentaerythritol. The size of the optimized nanoparticle formulations was in the range of 160 to 280 nm with the encapsulation efficiency increased to approximately 24% in the case of VAN-AOT and even to 42% in the case of GEN-AOT. The stability of AOT complexes encapsulated in PLGA NPs in aqueous media was investigated using DLS. Subsequently, the microdilution broth method confirmed the antimicrobial efficacy of the free VAN-AOT and GEN-AOT complexes, as well as PLGA NPs loaded with these complexes. Release studies of allogenic bone grafts impregnated with VAN-AOT formulation revealed a three-day release of VAN, whereas GEN-AOT exhibited an almost linear release pattern of GEN, reaching 33% by day 22. These results indicate that bone grafts impregnated with PLGA NPs loaded with HIP-complexed antibiotics represent a promising approach for localized and sustained antibiotic delivery in the treatment of musculoskeletal infections.